Preparation and characterization of TIG-alloyed hybrid composite coatings for high-temperature tribological applications - Adeyemi, Bello K.; Maleque, Md. Abdul; Ahmad, Zuraida; Adebisi, Adetayo A.; Mirdha, S. (2015)
There is an increasing interest in tribology community for developing high performance composite coating to meet severe tribological conditions of advanced mechanical system which requires high operating temperature and long life. In the present work, powder preplacement and tungsten inert gas (TIG) torch melting techniques have been employed to generate titanium carbide (TiC) based composite coatings containing hexagonal boron nitride(hBN) or Ni-P coated hBN (Ni-P-hBN) lubricant additive. The effect of preplaced powder composition on the cross-sectional microstructures and surface hardness of the developed coatings were analysed. Moreover, the friction and wear behaviours of the composite coatings at 600oC were evaluated using a Ducom ball-on-disc wear test rig. The results indicate that TIG-melted surface containing TiC and Ni-P-hBN powder mixtures exhibits optimum properties combining good control of microstructures and uniformly distributed hardness as well as excellent tribological properties due to enhanced wettability action of Ni-P encapsulated hBN particles.